Religiusitas Pembelian Impulsif dan Stimulus Eksternal Generasi Z dalam Pembelian Online: Studi Kasus Mahasiswa Universitas Jember - N. Ari Subagio; Moch. Shulthoni; Regina Niken Wilantari; Pradinda Oktaviasari Tijany (Universitas Jember, 2023)
This study aims to analyze and test the effect of religiosity and marketing external stimulus on impulsive online purchases in generation Z with respondents namely 75 Islamic Economics students at the Jember University Jember campus from class 2017 - 2019 with years of birth 1997 - 2002. The research used was quantitative method, the sampling technique is purposive sampling technique. Based on the results of the analysis and discussion, there is a significant influence of religiosity and external marketing stimulus on online impulsive purchases for Islamic Economics students at the Jember University Jember campus from class of 2017 – 2019. Students of Islamic Economics Students have a tendency not to make impulsive purchases due to the awareness of the respondents about the importance and influence of Islamic religious religiosity, even with an external stimulus that influences the buying decision which is spontaneously made by the respondent. Keywords: Religiosity, Impulsive Buying, External Stimulus, Generation Z, Online Buying